English-speaking countries: a different picture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Unlike their French counterparts, English colonialists did not seek to impose the concept of private ownership, and adopted a policy of each individual holding the land where he was. Thus the land was divided between the natives and the...